48 Who and When to Refer for Advanced Heart Failure? A Survey of Clinicians Referring to the Freeman Hospital. (6th June 2015) - McMinn, Jenna; Wrightson, Neil; Parry, Gareth; Clark, Stephen; Scheuler, Stephen; MacGowan, Guy
Abstract : The Freeman Hospital in Newcastle is one of the leading centres for cardiac transplantation and implantation of ventricular assist devices in the UK, receiving referrals to the Advanced Heart Failure Service predominantly from the North of England, but also Northern Ireland and complex cases from other regions. We were keen to establish whether referring clinicians felt they had sufficient knowledge about the service, its role and which patients may benefit from referral. We designed an online survey and sent a link via email to 127 potential referrers (predominantly colleagues who had referred to the service in the past). 56 of the 127 clinicians responded, giving a response rate of 44% (Table 1 ). Although 76% of those responding to the survey had previously referred at least one patient, only 70% reported being fully aware of the role of the Advanced Heart Failure Service, 62% felt they had a clear understanding of which patients to refer and 60% were confident in how to refer. Only 21% felt they had sufficient information about the service and guidelines for referral. The uncertainty amongst clinicians about who to refer influences whether patients are referred for advanced heart failure therapies, and therefore impacts on patient care as patients who may benefit from therapies such as transplantation or ventricular assist devices may not be referred for assessment. Factors prompting clinicians to refer patients with heart failure and relatively few co-morbidites, or which deter them from referring, are detailed in Figures 1 and 2 . Only 51% would consider referring a patient with more than 1 heart failure hospitalisation in the last year and fewer than 50% would consider referring patients with multiple ICD shocks, new renal impairment, or hypotension requiring reduction or discontinuation of ACE inhibitors/beta blockers, despite all of these being recognised adverse prognostic signs in patients with heart failure. The most common factor deterring clinicians from referring was the presence of multiple co-morbidities (74%). Disappointingly, other reasons for not referring included being unsure of who to refer (14%) or how to refer (10%). 84% of clinicians would be more likely to refer in the future if NICE approved VADs as 'destination therapy' rather than only as a 'bridge to transplant'. Other advances in heart failure management that may increase the likelihood of clinicians referring in the future are summarised in Table 2 . There is a clear demand for increased access to information about the Freeman Hospital Advanced Heart Failure Service and guidelines on who to refer, with 84% being "extremely interested" and the remaining 16% "quite interested" in receiving more information. With better education amongst referring clinicians, and NICE approval of destination therapy, referrals will likely increase significantly.